2014
DOI: 10.1007/s11605-013-2326-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum COL6A3 in Pancreatic Ductal Adenocarcinoma

Abstract: Type VI collagen (COL6) forms a microfibrillar network often associated with type I collagen and constitutes a major component of the desmoplastic reaction in pancreatic ductal adenocarcinoma (PDA). We have demonstrated recently that the α3 chain of COL6, COL6A3, is highly expressed in PDA tissue and undergoes tumor-specific alternative splicing. In this study, we investigated the diagnostic value and clinical significance of circulating COL6A3 protein and mRNA in PDA. COL6A3 levels in sera from patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…In addition, a growing body of evidence shows that ColVI is a potential biomarker for cancer diagnosis. ColVI levels in the sera of individuals with melanoma or pancreatic cancer are dramatically increased when compared with those of healthy controls (Burchardt et al, 2003;Makawita et al, 2011;Kang et al, 2014). Collectively, these findings point to ColVI as an ECM molecule that promotes tumor growth.…”
Section: Box 2 Collagen VI In Cancermentioning
confidence: 84%
“…In addition, a growing body of evidence shows that ColVI is a potential biomarker for cancer diagnosis. ColVI levels in the sera of individuals with melanoma or pancreatic cancer are dramatically increased when compared with those of healthy controls (Burchardt et al, 2003;Makawita et al, 2011;Kang et al, 2014). Collectively, these findings point to ColVI as an ECM molecule that promotes tumor growth.…”
Section: Box 2 Collagen VI In Cancermentioning
confidence: 84%
“…Previous studies suggested that the induction of collagens including COL1A1 and COL4A1 is regulated by chemokine signaling (CXCR7) and downstream pathways such as PI3K/AKT and NF-κB [31, 32]. COL6A3, an ECM protein, has been identified as the clinically relevant collagen in colorectal, ovarian, and pancreatic cancer [3638]. COL6A3 protein and mRNA are significantly upregulated not only in colorectal cancer cells but also in the stromal cells of tumor lesions, which promote tumor growth by modulating Hippo and Wnt signaling [36, 39].…”
Section: Discussionmentioning
confidence: 99%
“…1). 5,6,[8][9][10][11] This stroma creates a shield which prevents correct vascularization, hence reduces chemotherapies penetrance, and triggers the appearance of hypoxic zones, one of the most important characteristics of PDAC ( Fig. 1).…”
mentioning
confidence: 99%